PENGARUH SENAM LANSIA TERHADAP KADAR GULA PADA PENDERITA DIABETES MILITUS - Basyariah Lubis; David Ginting; Sri Melda Br Bangun; Ronny Ajharta (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2020)
Diabetes mellitus is a collection of symptoms that arise in a person due to the body experiencing interference in controlling blood sugar levels. Exercise is a good way to help overcome the problem of diabetes mellitus. Because with diabetes sports can get a healthy body and entertainment facilities that are done together with people who experience the same suffering. The type of exercise recommended is aerobics, which is exercise that can increase the capacity of the heart and lungs and make insulin work more efficiently. The research method uses the experimental method. The total sample of 24 people taken using total sampling techniques. Where the samples taken were 24 elderly people. The instrument used is the KGD tool, where there are values ​​of different average blood sugar levels before 261.33 mg / dl and after 23.538 mg / dl elderly gymnastics are performed. Conclusion there is the influence of elderly exercise on blood sugar levels in diabetes.